Test the Effectiveness of Rambutan Leaf (Nephelium lappaceum L.) Extract as Antifungal againts Sclerotium rolfsii Invitro - Ayunda Intan Kartika; Moralita Chatri (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Sclerotium rolfsii is a pathogenic fungus that causes stem rot, root rot, wilting and even death of the affected plants. This fungus usually attacks horticultural crops. In its control, many farmers use synthetic fungicides. However, the use of synthetic fungicides in the long term is not recommended because of the negative impact on the environment. So there is a need for other alternatives, namely natural fungicides that are environmentally friendly, one of which is Nephelium lappaceum L. leaf extract in inhibiting the growth of S. rolfsii. The purpose of this study was to test the effectiveness of N. lappaceum leaf extract against S. rolfsii and to determine the antifungal activity of the concentration of N. lappaceum leaf extract against S. rolfsii. This research was carried out from November 2021 to February 2022 at the Integrated Research Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This study was an experimental study consisting of 5 treatments with 3 replications with N. lappaceum leaf extract at a concentration of 0% (Control), 10%, 20%, 30% and 40%. Colony diameter data analysis used ANOVA variance and continued with DMRT test at 5% level, while antifungal activity was analyzed descriptively. The results showed that the leaf extract of N. lappaceum was able to inhibit the growth of S. rolfsii. All treatments were significantly different from the control and each treatment also showed significant differences. At concentrations of 10% and 20% are classified as weak and at concentrations of 30% and 40% are classified as moderate.